Cardiovascular profile of vasculitis patients at tertiary care center - Wani, Mohamad A.; Wani, Firdous D.; Nath, M. Yousuf (International Journal of Research in Medical Sciences, 2022)
Background: The vasculitides are a heterogenous group of conditions characterized by blood vessel inflammation and necrosis. Vasculitides are relatively uncommon conditions whose etiology is still poorly understood. Objective of the research was to study the cardiovascular profile of vasculitis patients at a tertiary care centre. Methods: The present hospital based observational study was conducted in the department of internal medicine, Sher-i-Kashmir Institute of Medical Sciences (SKIMS), Srinagar, Jammu and Kashmir, India. The study had two parts: retrospective and prospective. In the retrospective part, all patients of vasculitis who were admitted or evaluated in outpatient department (OPD) from March 2012 to September 2018, were enrolled for the analysis. In the prospective part, all patients of vasculitis admitted or evaluated in OPD from October 2018 to May 2020 were enrolled for study. Results: Out of total 77 patients studied, 39 (50.6%) were prospective cases and 38 (49.4%) cases were of retrospective nature. Normal echocardiographic and electrocardiography (ECG) findings were seen in majority of all three groups. Computed tomography (CT) angio shows involvement of right subclavian artery in 9 (40.9%) patients, 8 (36.4%) patients had involvement of left subclavian artery, 6 (27.3%) patients had involvement of arch of aorta, CT angio was suggestive of involvement left common carotid artery 5 patients, 2 patients each had involvement of celiac artery, bilateral iliac, ascending aorta, normal CT angio findings. Arterial Doppler was suggestive of involvement of right common carotid artery (CCA) and left CCA in 4 (30.8%) patients each, right superior cerebellar artery (SCA) involvement in 3 (23.1%) patients, left SCA involvement in 4 (30.8%) patients, left right brachiocephalic artery (RBA), right RA and B/L UA involvement was observed in 1 (7.7%) patient each. Conclusions: The association between cardiovascular disease and a vasculitis is well documented. our study discusses the association between cv disease and vasculitis.